Solve for x.
–2(x - 1) - x + 3 = -1
Anyone wanna help?
![Solve for x 2x 1 x 3 1 Anyone wanna help class=](https://us-static.z-dn.net/files/d8e/f4c8c56d5f608e2d2a530f1cd05708d4.png)
Answer:
-2(x-1) - x + 3 = -1
First if all, we operate the parenthesis knowing that [tex]a(b+c) = ab + ac[/tex]:
-2(x-1) - x + 3 = -1 ---->.-2x -2*(-1) - x + 3 = -1
Now, we operate:
.-2x -2*(-1) - x + 3 = -1 ----> -2x + 2 - x + 3 = -1
Now we operate another time to put all the x together and the independent terms too:
-2x + 2 - x + 3 = -1 ----> -3x + 5 = -1
We substract 5 at both sides to have only the x at one side:
-3x + 5 = -1 ----> -3x + 5 - 5 = -1 - 5 ----> -3x = -6
As both sides have a minus (-) we can eliminate it:
-3x = -6 ----> 3x = 6
We divide both sides by 3 to have only a x:
3x = 6 ----> 3x/3 = 6/3 ----> x = 2
Now, we know that x=2. We can also verify it by replacing it on the first equation:
-2(x-1) - x + 3 = -1 ---> -2(2-1) - 3 + 3 = -1 ---> -2(1) - 2 + 3 = -1 ---> -2 - 2 + 3 = -1
Now we know it's true, as we have replaced it and we got he answer.